Force-velocity profile changes with forearm wearable resistance during standing start sprinting - Macadam, P.; Mishra, M.; Feser, E. H.; Uthoff, A. M.; Cronin, J. B.; Zois, J.; Nagahara, R.; Tinwala, F. (European Journal of Sport Science, 2020)
Horizontal force-velocity (F-V) profiling is a strategy to assess athletes` individual performance capabilities during sprinting. This study investigated the acute changes in F-V profiles during sprinting of fourteen collegiate male sprinters with a mean 100-m sprint time of 11.40 ± 0.39 s, from a split-stance starting position. The subjects sprinted 30-m with, and without, wearable resistance (WR) equivalent to 2% body mass, attached to their forearms. Sprinting time at 5, 10, 20, and 30-m was assessed using laser technology. External horizontal F-V relationships were calculated via velocity-time signals. Maximal theoretical velocity (V0), theoretical relative and absolute horizontal force (F0), and horizontal power (Pmax) were determined from the F-V relationship. Paired t-tests were used to determine statistical differences (p = 0.05) in variables across conditions with Cohen`s d as effect sizes (ES) calculated to assess practical changes. Sprint times at 10-m and beyond were significantly increased (1.9-3.3%, p 0.01-0.03, ES 0.46-0.60) with WR compared to unloaded sprinting. The only significant change in F-V with the WR condition was found in relative Pmax system (-6.1%, p 0.01, ES 0.66). A small decrease was reported in V0 (-1.0%, p 0.11, ES 0.27), with small to medium ES decreases reported in F0 (-4.8% to -6.1%, p 0.07-0.21, ES 0.25-0.51) and Pmax (-4.3% to - 4.6%, p 0.06-0.08, ES 0.32-0.45). The greater changes to F0 and Pmax suggest that forearm WR may be a possible training tool for athletes who wish to focus on force and power adaptation during sprint acceleration from a standing start.